Semantic features of two-object verbal phraseological units with the meaning of the relation - Marsheuskaya, Valiantsina V. (Journal of the Belarusian State University. Philology, 2024)
In the article the author examines the verbal phraseological units of the modern Belarusian language with the semantic meaning of the relation of a two-object external orientation (to a human object or to a non-human object). The author has established that with the direction of the action (process) phraseological units form five semantic subgroups on the objectperson (dominant influence, verbal influence, emotional influence, assistance, and contact) within the semantic group of interpersonal (social) relations. The author substantiates the idea that when an action (process) is directed at a specific subject, phraseological units can develop a new meaning and relate to the semantic group of personal-subject relations or completely change their subcategorical meaning. The transition of phraseological units into the subcategory of the state is facilitated by the actualisation of the connotative macro component in the structure of phraseological meaning by the contextual environment. Phraseological units begin to function in impersonal use with a modal meaning of the necessity or impossibility of carrying out an action (process), which is characteristic of the units of the subcategory of the state. The results obtained can be used in the practice of teaching phraseology in institutions of higher and general secondary education, as well as in the theory and practice of phraseography.